English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-02 02:30:33 · 6 answers · asked by Carpe Diem (Seize The Day) 6 in Science & Mathematics Mathematics

6 answers

To calculate the inverse of y = -x,
you have to interchange the variables and solve for y.

Therefore, we have to solve for y in the equation x = -y
y = -x

The inverse is itself.

2006-12-02 02:33:29 · answer #1 · answered by Puggy 7 · 0 0

Look at it graphically. The inverse of the function it its mirror image wrt to the diagonal line y=x.

The line y=-x forms a big 'X' with the line y=x. If you take that big 'X' and rotate it around the '/' line, you'll see that the '\' line will just rotate back onto itself and the result is the same 'X' image.

2006-12-02 11:55:01 · answer #2 · answered by Anonymous · 0 0

It is its own inverse

2006-12-02 10:39:34 · answer #3 · answered by dennismeng90 6 · 0 0

f(x) = - x
has inverse

f^(-1)(x) = -x

because f(f(x) = f(-x) = x

2006-12-02 10:34:53 · answer #4 · answered by Mein Hoon Na 7 · 0 0

x=-y

2006-12-02 11:36:44 · answer #5 · answered by openpsychy 6 · 0 0

x=-y

2006-12-02 10:36:08 · answer #6 · answered by Anonymous · 0 0

fedest.com, questions and answers